Influenza vaccination in the elderly. Issue 3 (4th March 2018) - Smetana, Jan; Chlibek, Roman; Shaw, Jana; Splino, Miroslav; Prymula, Roman
ABSTRACT: Seasonal influenza is a prevalent and serious annual illness resulting in widespread morbidity and economic disruption throughout the population; the elderly and immunocompromised are particularly vulnerable to serious sequelae and mortality. The changing demographics worldwide to an aging society have important implications for public health policy and pharmaceutical innovations. For instance, primary prevention via immunization is effective in reducing the burden of influenza illness among the elderly. However, the elderly may be insufficiently protected by vaccination due to the immunosenescence which accompanies aging. In addition, vaccine hesitancy among the younger populations increases the likelihood of circulating infectious diseases, and thus concomitant exposure. While it is clear that the development of more immunogenic vaccines is an imperative and worthy endeavor, clinical trials continue to demonstrate that the current influenza vaccine formulation remains highly effective in reducing morbidity and mortality when well matched to circulating strains.